Relationship between age and remimazolam dose required for inducing loss of consciousness in older surgical patients - Song, Jin-Chao; Wang, Xiao-xi; Fu, Xiang; Chen, Wei; Tang, Shu-heng; Deng, Fang; Yang, Hua; Liu, Wen (Frontiers in Medicine, 2024)
Background Remimazolam is a new ultra-short-acting benzodiazepine for procedural sedation and general anaesthesia, characterised by rapid onset of action, quick recovery, and organ-independent metabolism. Older patients tend to sustain more treatment-emergent adverse events (TEAEs) and worse perioperative prognoses after receiving remimazolam. However, few studies have investigated the appropriate dose of remimazolam for loss of consciousness (LOC) in geriatric patients. We designed this study to provide evidence for dose references and elucidate the relationship between age and remimazolam requirement for inducing LOC during anaesthesia induction. Methods Exactly 120 patients scheduled for general surgery under general anaesthesia were included and divided into two groups: Group A (60 patients, 18–64 years) and Group B (60 patients, ≥ 65 years). LOC, defined as a Modified Observer’s Assessment of Alertness and Sedation score at 1 had been reached, emerged after all participants received a continuous infusion of remimazolam at a rate of 0.05 mg/kg/min. Results The remimazolam required for inducing LOC was 0.26 and 0.19 mg/kg in groups A and B, respectively, and the remimazolam dose in group B decreased by 26.9% compared to group A. According to the bivariate linear correlation analysis, remimazolam requirement was negatively correlated with age. Multivariable linear regression models and further adjustments for potential impact factors indicated that age was an independent factor for the remimazolam dose required for LOC. Conclusion This study demonstrated that age was significantly and independently correlated with the remimazolam requirement for inducing LOC. To obtain haemodynamic stability during the induction of general anaesthesia, appropriately reducing the remimazolam dose is recommended for geriatric patients.